Identification of Protein Kinase C Activation as a Novel Mechanism for RGS2 Protein Upregulation through Phenotypic Screening of Natural Product Extracts - Raveh, Avi (2014)
Biochemical high-throughput screening is widely used in drug discovery, using a variety of small molecule libraries. However, broader screening strategies may be more beneficial to identify novel biologic mechanisms. In the current study we used a β-galactosidase complementation method to screen a selection of microbial-derived pre-fractionated natural product extracts for those that increase regulator of G protein signaling 2 (RGS2) protein levels. RGS2 is a member of a large family of proteins that all regulate signaling through G protein–coupled receptors (GPCRs) by accelerating GTPase activity on active Gα as well as through other mechanisms. RGS2−/− mice are hypertensive, show increased anxiety, and are prone to heart failure. RGS2 has a very short protein half-life due to rapid proteasomal degradation, and we propose that enhancement of RGS2 protein levels could be a beneficial therapeutic strategy. Bioassay-guided fractionation of one of the hit strains yielded a pure compound, Indolactam V, a known protein kinase C (PKC) activator, which selectively increased RGS2 protein levels in a time- and concentration-dependent manner. Similar results were obtained with phorbol 12-myristate 13-acetate as well as activation of the Gq-coupled muscarinic M3 receptor. The effect on RGS2 protein levels was blocked by the nonselective PKC inhibitor Gö6983 (3-[1-[3-(dimethylamino)propyl]-5-methoxy-1H-indol-3-yl]-4-(1H-indol-3-yl)-1H-pyrrole-2,5-dione), the PKCβ-selective inhibitor Ruboxastaurin, as well as small interfering RNA-mediated knockdown of PKCβ. Indolactam V-mediated increases in RGS2 protein levels also had functional effects on GPCR signaling. This study provides important proof-of-concept for our screening strategy and could define a negative feedback mechanism in Gq/Phospholipase C signaling through RGS2 protein upregulation.